2021
DOI: 10.1152/advan.00022.2021
|View full text |Cite
|
Sign up to set email alerts
|

Physiology labs during a pandemic: What did we learn?

Abstract: This article captures a collective reflection on the successes and challenges we experienced when teaching physiology laboratories online during the COVID-19 pandemic. Physiology instructors from six institutions discussed their own efforts to redesign meaningful physiology laboratories that could be taught remotely, as the nation scrambled to respond to the sudden shift out of the classroom. Despite the complexity of this task, clear themes emerged as our courses transitioned to an online format in spring 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Interestingly, we showed that teamwork dynamics independently correlated with teamwork satisfaction, an association consistently shown across different SGT settings (Tables 4 and 5 ). A prior study indicated that in online SGT, team dynamics were a potentially vital element for providing students with a sense of interdependence and mutual collaboration [ 28 ]. Better practices in team dynamics enhances student engagement with online course content and potentially promotes satisfaction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we showed that teamwork dynamics independently correlated with teamwork satisfaction, an association consistently shown across different SGT settings (Tables 4 and 5 ). A prior study indicated that in online SGT, team dynamics were a potentially vital element for providing students with a sense of interdependence and mutual collaboration [ 28 ]. Better practices in team dynamics enhances student engagement with online course content and potentially promotes satisfaction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prior study indicated that in online SGT, team dynamics were a potentially vital element for providing students with a sense of interdependence and mutual collaboration [ 28 ]. Better practices in team dynamics enhances student engagement with online course content and potentially promotes satisfaction [ 28 ]. This is in line with theories pertaining to online education indicating that learner motivation, curricular design, shared community building, and reflective practices are essential for maximizing learners’ gain [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An effective way to uncover the different ways students reason about a topic is through thoughtful and timely formative assessments ( Chen et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%